从《海峡华人杂志》看19世纪末至20世纪初 海峡华人的社会改革 = A study on the reformation of the Straits Chinese from late 19th to early 20th century through the Straits Chinese magazine - 黄慧莹 Wong, Hui Yen (Nanyang Technological University, 2020)
本文将以文本分析为主，透过《海峡华人杂志》分析海峡华人进行的社会改革，尤其着重于华人传统文化习俗层面。此外，本文尝试将同一事件（或改革主题）的不同观点进行整合，梳理出在改革过程中不同的意见及立场。这些立场可直接或间接地影响改革的效果，可为未来相关论文提供研究材料。 本文将以五章分析《海峡华人杂志的》创办背景及海峡华人的社会改革。 第一部分为绪论。第二部分将介绍《海峡华人杂志》，说明其创办缘由以及编者简介，同时分析19世纪末到20世纪初新马两地的三语报刊杂志的出版情况。第三部分从《海峡华人杂志》分析海峡华人的社会改革。本文将重心放在华人传统习俗如婚礼、葬礼上，看海峡华人如何在东西文化的冲击下保留和割舍原有的传统。接下来，本文分析海峡华人对于女性社会地位的改革，包括建立女子学校和给予女子平等的地位等。最后部分为结论，将总结研究成果。 This paper will focus on analyzing the reformation of the Straits Chinese from late 19th to early 20th century through the Straits Chinese Magazine. Emphasis will be placed on the Chinese traditional customs and gender views. Moreover, different perspectives of the Straits Chinese Society will be integrated and used as research materials for any future related studies. This paper uses five chapter to analyze the founding history of the Straits Chinese Magazine and reformation of the Straits Chinese. The first section covers the introduction of the paper. This is followed by the introduction of the Straits Chinese Magazine, explaining the founding history, editor’s profile and analysis of the trilingual newspapers and magazines publication in Singapore and Malaysia between the late 19th and early 20th centuries. The third section focus on the reformation of traditional Chinese customs, such as Chinese marriage custom and funeral rites, and explore how the Straits Chinese have retained and abandoned their original traditions under the impact of the Eastern and Western culture. Following which, social status reforms of women in the Straits such as establishment of girls’ schools and elevation of their status will be analyzed. The last part is the conclusion, where the research results are summarized.